High temperature corrosion during biomass firing: improved understanding by depth resolved characterisation of corrosion products. (January 2015) - Okoro, S. C.; Montgomery, M.; Frandsen, F. J.; Pantleon, K.
Abstract : The high temperature corrosion of an austenitic stainless steel (TP 347H FG), widely utilised as a superheater tube material in Danish power stations, was investigated to verify the corrosion mechanisms related to biomass firing. KCl coated samples were exposed isothermally to 560°C, for one week, under conditions simulating straw-firing. Thorough characterisation of the exposed samples was conducted by the analysis of sample cross-sections applying microscopy and spectroscopy based techniques. Cross-section analysis revealed the microstructure, as well as chemical and morphological changes within the near surface region (covering both the deposit and the steel surface). Such cross-section analysis was further complemented by plan view investigations (additionally involving X-ray diffraction) combined with removal of the corrosion products. Improved insights into the nature of the corrosion products as a function of distance from the deposit surface were revealed through this comprehensive characterisation. Corrosion attack during simulated straw-firing conditions was observed to occur through both active oxidation and sulphidation mechanisms.